STUDENTS' INTERPRETATION OF TRAFFIC SIGNS IN LANGSA - Bayos erwana syahroni (Journal of Education, Linguistics, Literature and Language Teaching, 2019)
Keyword : Interpretation, traffic signs Abstract This research entitled students’ interpretation of traffic signs in Langsa town. The subject of this research are 30 students in SMA Negeri 1 Langsa. The problems of this research are how meanings are contained in the traffic signs displayed in Langsa and are the students of senior high school in Langsa able to interpret the meaning of traffic signs. This research used descriptive qualitative methodology and analyzed the data by using interactive model miles and by using several steps namely: data collection, data reduction, data display and conclusion. To analyze the meanings of symbol, the researcher used Charles sanders pierce theory as reference to reveal the meaning of traffic signs and gave the quostioners as instrument of research to the students to investigate the students’ interpretation of traffic signs. The result of this research has been found that not all traffic signs can be understood by the students in Langsa.